Nomadland [videorecording (Blu-Ray)] - Zhao, Chloé; McDormand, Frances; Strathairn, David; May, Linda (Nomad); Swankie; Bruder, Jessica (20th Century Studios, 2021)
Following the economic collapse of a company town in rural Nevada, Fern packs her van and sets off on the road exploring a life outside of conventional society as a modern-day nomad. Along the way, she meets other nomads who become mentors in the vast landscape of the American West.